Implementasi Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam Kelas 8 - Aulia Hafsah Amanah; Ayi Sobarna; Helmi Aziz (UNISBA Press, 2024)
Abstract. This research is motivated by the varying learning needs of students. Differentiated instruction is one way for teachers to meet the needs of each student because the teaching process can be adapted to students' interests and talent. Based on this phenomenon, the research questions are formulated as follows: (1) How is the planning of differentiated instruction in the Merdeka Curriculum for Islamic Education for 8th-grade at SMPN 26 Bandung? (2) How is the implementation of differentiated instruction in the Merdeka Curriculum for Islamic Education for 8th-grade at SMPN 26 Bandung? (3) How is the evaluation of differentiated instruction in the Merdeka Curriculum for Islamic Education for 8th-grade at SMPN 26 Bandung? (4) What are the supporting and inhibiting factors of differentiated for Islamic Education for 8th-grade at SMPN 26 Bandung? This study uses a qualitative approach with a descriptive method, and the data collection techniques include interviews, observations, and documentation. Based on the research findings and discussion the conclusions are: 1. The planning of differentiated instruction includes ATP, CP, RPP, modules, teaching methods, and supporting learning tools. 2. The implementation of differentiated instruction is done by providing support through various learning resources. 3. The evaluation of PAI learning not only assesses the learning outcomes but also evaluates students' knowledge and attitudes on a daily basis. 4. Supporting factors include support from the school and parents. Inhibiting factors include the teacher's limited ability to engage all students in the learning process. Abstrak. Penelitian ini dilatarbelakangi oleh adanya perbedaan kebutuhan belajar siswa. Pembelajaran diferensiasi merupakan salah satu cara guru untuk memenuhi kebutuhan setiap siswa karena proses pengajaran dapat disesuaikan dengan minat siswa. Berdasarkan fenomena tersebut, rumusan masalah penelitian adalah sebagai berikut: (1) Bagaimana perencanaan pembelajaran diferensiasi dalam Kurikulum Merdeka untuk Pendidikan Agama Islam kelas VIII di SMPN 26 Bandung? (2) Bagaimana pelaksanaan pembelajaran diferensiasi dalam Kurikulum Merdeka untuk Pendidikan Agama Islam kelas VIII di SMPN 26 Bandung? (3) Bagaimana evaluasi pembelajaran diferensiasi dalam Kurikulum Merdeka untuk Pendidikan Agama Islam kelas VIII di SMPN 26 Bandung? (4) Apa saja faktor pendukung dan penghambat pembelajaran diferensiasi untuk Pendidikan Agama Islam kelas VIII di SMPN 26 Bandung? Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, serta teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Berdasarkan hasil penelitian dan pembahasan, dapat disimpulkan sebagai berikut: 1. Perencanaan pembelajaran diferensiasi meliputi ATP, CP, RPP, modul, metode pembelajaran, dan alat peraga pendukung. 2. Pelaksanaan pembelajaran diferensiasi dilakukan dengan memberikan dukungan melalui berbagai sumber belajar. 3. Evaluasi pembelajaran PAI tidak hanya menilai hasil belajar, tetapi juga menilai pengetahuan dan sikap siswa secara harian. 4. Faktor pendukung meliputi dukungan dari sekolah dan orang tua. Faktor penghambat meliputi keterbatasan kemampuan guru dalam melibatkan semua siswa dalam proses pembelajaran.